Beauty Expert System to Determine the Skin Problem and the Treatment for Patient at Jasmine Clinic - Cindy Himawan Himawan; Shinta Bomi (President University, 2020)
As people get busy, they want fast and easyservice. This also applies to skin services in beautyclinics. The patient wants ease in terms of determiningthe type of facial skin problem and what treatments areappropriate for them. However, due to the limitednumber of dermatologists, patients often have to wait along time to be examined and sometimes even cannot beserved due to limited schedules. This expert system isbased on how doctors determine the type of facialproblems in patients and what treatments areappropriate for the problem. By using a mobileapplication, this system can be accessed by patients fromhome, making it easier for patients to get a quick andaccurate examination. This application was built usingthe forward chaining method where later patients willanswer questions that are used as a decision branch todetermine the skin problem. Eventually the patient canmake the required treatment and skin care needs andtake them to the clinic.